2011
DOI: 10.1097/hmr.0b013e31821826a1
|View full text |Cite
|
Sign up to set email alerts
|

Deskilling and adaptation among primary care physicians using two work innovations

Abstract: Primary care physicians perceive and experience deskilling as a tangible outcome of using particular health care innovations. However, such deskilling is, in part, a function of physicians' own actions as well as extant pressures in the surrounding work context. Health care organizations and managers have a productive role to play in attempting to mitigate these pressures and lessen the deskilling outcomes associated with them. This study supports closer examination of the total costs and benefits deriving fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 28 publications
1
37
0
4
Order By: Relevance
“…Note that computer-based systems, such as MDSS, are often seen by clinicians as an extra burden in their day-to-day practice [18]. The problem may appear when the MDSS conflicts with guidelines of medical practice [19], something bound to happen unless those guidelines are somehow fed as prior knowledge to the intelligent systems. In this scenario, interpretability might be seen as an opportunity to make model performance and compliance with guidelines compatible goals.…”
Section: Interpretability and Explainabilitymentioning
confidence: 99%
“…Note that computer-based systems, such as MDSS, are often seen by clinicians as an extra burden in their day-to-day practice [18]. The problem may appear when the MDSS conflicts with guidelines of medical practice [19], something bound to happen unless those guidelines are somehow fed as prior knowledge to the intelligent systems. In this scenario, interpretability might be seen as an opportunity to make model performance and compliance with guidelines compatible goals.…”
Section: Interpretability and Explainabilitymentioning
confidence: 99%
“…Hoff 45 conducted interviews with primary care physicians in the USA to examine implementation of two innovations, ie, electronic health record use and evidence-based practice guidelines, and found that primary care physicians use these innovations in ways that indicate "deskilling outcomes," including stereotyping of patients and decreasing confidence in clinical decision-making. The pressure to increase patient volume and comply with complex requirements of chronic disease guidelines left several physicians feeling unable to provide the type of holistic patient care that leveraged their full range of clinical knowledge and skills.…”
mentioning
confidence: 99%
“…As we offload more and more work to machines, we might also need to take care that we "don't let the machine take our work", and most importantly, don't surrender ourselves to the developing intelligence of high technology. Meanwhile, we should be aware that our concerns about technology have little to do with technology itself, but rather with the way we design and use them in practice (Bailey, 2011;Hoff, 2011). Doctors should take the agency on when, how and why to use technology and not allow technology take it away from them.…”
Section: Resultsmentioning
confidence: 99%
“…Hoff also found that physicians increasingly lost their ability to understand and abstract the richness and uniqueness of patients' information given the standardized EHR format, consequently undercutting their "ability to make informed decisions around diagnosis and treatment" (Hoff, 2011) Both doctor-patient communication and physical examination skills have been and remain important venues for obtaining information critical for making correct diagnoses. Using them together is sufficient for making good diagnoses.…”
Section: Concerns On the Negative Effects Of Medical Technology On Hementioning
confidence: 99%